Exogenous Application of Abscisic Acid or Gibberellin Acid Has Different Effects on Starch Granule Size Distribution in Grains of Wheat - Dian-liang PENG; Tie CAI; Yan-ping YIN; Wei-bing YANG; Ying-li NI; Dong-qing YANG; Zhen-lin WANG (Journal of Integrative Agriculture, 2013)
Granule size distribution of wheat starch is an important characteristic that can affect its chemical composition and the functionality of wheat products. Two high-yield winter wheat cultivars were used to evaluate the effects of the application of exogenous ABA or GA during the reproductive phase of the initial grain filling on starch granule size distribution and starch components in grains at maturity. The results indicated that a bimodal curve was found in the volume and surface area distribution of grain starch granules, and a unimodal curve was observed for the number distribution under all treatments. The exogenous ABA resulted in a significant increase in the proportions (both by volume and by surface area) of B-type (<9.9 μm in diameter) starch granules, with a reduction in those of A-type (>9.9 μm) starch granules, while, the exogenous GA3 led to converse effects on size distribution of those starch granules. The exogenous ABA also increased starch, amylose and amylopectin contents at maturity but significantly reduced the ratio of amylose to amylopectin. Application of GA3 significantly reduced starch content, amylopectin content but increased the ratio of amylose to amylopectin. The ratio of amylose to amylopectin showed a significant and negative relationship with the volume proportion of granules <9.9 μm, but was positively related to the volume proportion of granules 22.8-42.8 μm.